Evidence of bacterial biofilms in chronic rhinosinusitis: factors affecting and the impact on prognosis - Gogia, Vivek; Vaid, Lakshmi; Singh, P. P.; Saha, Rumpa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The aim of the study was to study the evidence of bacterial biofilms in chronic rhinosinusitis (CRS) and its effect on disease prognosis by correlating between symptom score, computed tomography (CT) score and endoscopy score. Methods: 40 samples of bacteriologically positive CRS patients were studied and data analyzed using SNOT-20 questionnaire, nasal endoscopy scores and CT grading. Functional endoscopic sinus surgery was done in all CRS patients to clear blockage and ensures patency of osteomeatal complex. Postoperative evaluation continued at 2 weeks, 1 month and 3 months. A comparison made between preoperative and postoperative SNOT-20 and endoscopy scores of patients with and without biofilms. Results: Patients with biofilm forming bacteria have significantly poor preoperative and postoperative SNOT-20 score and endoscopy score as compared to bio-film negative patients; however the quality of life improved in both the groups. Conclusions: Biofilms play a potential role in postoperative prognosis of patients undergoing FESS. Further studies and research is required for assigning them as a definite proprietor for CRS.